Hukuman Disiplin Terhadap Narapidana Yang Melarikan Diri Dari Lembaga Pemasyarakatan Saat Terjadinya Bencana Alam - Hambuwali, William; Ariawan, I Gusti Ketut (Kertha Wicara : Journal Ilmu Hukum, 2020)
The purpose of writing this scientific work is to study the security procedures of correctional institutions in the event of natural disasters with a Human Rights perspective and also to review the setting of disciplinary punishments against escaped inmates in circumstances of natural disasters. The research method used is a normative research method that prioritizes a conceptual approach in addition to the statutory approach. The results showed that the procedure of handling correctional institutions in the event of a natural disaster is regulated in “Permenkumhan 33/15” jo. “SOP Penindakan Bencana Alam.” Both provisions have not fully realized the protection of human rights because both provisions disguise procedures for all types of natural disasters, whereas each natural disaster has a different type of ineligion. In addition, those provisions also do not take into account the age factor of the targeted citizens. The next problem is that provision of “Permenkumham 6/13” generalizes sanctions against escaped inmates, so that inmates who are forced to escape in natural disasters can be sentenced to severe discipline as well as inmates who escape under normal circumstances. This situation has no effect on inmates who have previously suffered from the threat of natural disasters. Keywords: Natural Disaster, Correctional Institution, Escape, Inmate, Double Suffering.